Intra- and extracellular osmotic regulation in the hololimnetic Caridea and Anomura: a phylogenetic perspective on the conquest of fresh water by the decapod Crustacea - de Faria, Samuel Coelho; Augusto, Alessandra da Silva [UNESP]; McNamara, John Campbell (Springer Heidelberg, 2011)
We investigate extra- and intracellular osmoregulatory capability in two species of hololimnetic Caridea and Anomura: Macrobrachium brasiliense, a palaemonid shrimp, and Aegla franca, an aeglid anomuran, both restricted to continental waters. We also appraise the sharing of physiological characteristics by the hololimnetic Decapoda, and their origins and role in the conquest of fresh water. Both species survive salinity exposure well. While overall hyperosmoregulatory capability is weak in A. franca and moderate in M. brasiliense, both species strongly hyporegulate hemolymph [Cl-] but not osmolality. Muscle total free amino acids (FAA) increase slowly but markedly in response to the rapid rise in hemolymph osmolality consequent to hyperosmotic challenge: 3.5-fold in A. franca and 1.9-fold in M. brasiliense. Glycine, taurine, arginine, alanine and proline constitute a parts per thousand 85% of muscle FAA pools in fresh water; taurine, arginine, alanine each contribute a parts per thousand 22% in A. franca, while glycine predominates (70%) in M. brasiliense. These FAA also show the greatest increases on salinity challenge. Muscle FAA titers correlate strongly (R = 0.82) with hemolymph osmolalities across the main decapod sub/infraorders, revealing that marine species with high hemolymph osmolalities achieve isosmoticity of the intra- and extracellular fluids partly through elevated intracellular FAA concentrations; freshwater species show low hemolymph osmolalities and exhibit reduced intracellular FAA titers, consistent with isosmoticity at a far lower external osmolality. Given the decapod phylogeny adopted here and their multiple, independent invasions of fresh water, particularly by the Caridea and Anomura, our findings suggest that homoplastic strategies underlie osmotic and ionic homeostasis in the extant freshwater Decapoda.
Keywords: Osmoregulation; Hololimnetic Decapoda; Conquest of fresh water; Anisosmotic extracellular regulation; Isosmotic intracellular regulation; Muscle free amino acids